2008
DOI: 10.1007/s00535-008-2179-4
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial dysfunction and apoptosis of acinar cells in chronic pancreatitis

Abstract: Apoptosis plays an important role both in the initial stages and during the progression of CP, as evident in all tissue grades. Increased DeltaPsim, loss of ATP, and activation of caspases suggests the involvement of intrinsic pathways.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…In addition, ER stress induced by mutation and misfolding of the carboxyl ester lipase (CEL) protein is also involved in CP development by regulating acinar cell apoptosis 17 . Consistently, pancreatic tissues from patients with CP exhibit significant DNA fragmentation, apoptotic nuclei, and increased p53 expression, as well as substantial alterations in other apoptosis-regulating factors 18 . These observations suggest that ER stress and apoptosis might be involved in the development of CP.…”
Section: Introductionmentioning
confidence: 65%
“…In addition, ER stress induced by mutation and misfolding of the carboxyl ester lipase (CEL) protein is also involved in CP development by regulating acinar cell apoptosis 17 . Consistently, pancreatic tissues from patients with CP exhibit significant DNA fragmentation, apoptotic nuclei, and increased p53 expression, as well as substantial alterations in other apoptosis-regulating factors 18 . These observations suggest that ER stress and apoptosis might be involved in the development of CP.…”
Section: Introductionmentioning
confidence: 65%
“…[20][21][22][23] In the acinar cells of CP, Bateman et al showed a statistically significant increase in apoptotic index compared with that in controls. In a recent report, Schrader et al 24 showed a lack of increased b-cells turnover in CP patients, despite an B10-fold increase in the number of apoptotic acinar cells, suggesting that the damage to the pancreas somehow specifically targets the exocrine compartment and affects the endocrine islets to a lesser extent.…”
Section: Pancreatic Stellate Cellsmentioning
confidence: 99%
“…TP53, the regulatory factor of apoptosis, could interact with Bcl 2 family proteins in the cytoplasm that causing mitochondrial outer membrane permeability increased and cell apoptosis [32]. In clinical, pancreatic tissues from patients with pancreatitis exhibited apoptotic nuclei, and increased p53 expression [33]. Consistently, Lei Zhou et al found that TP53 suppressed on mouse pancreatitis model obviously inhibited pancreatic acinar cell apoptosis and the in ammation [34].…”
Section: Discussionmentioning
confidence: 86%